Pengaruh permainan lego robot cardboard box terhadap kreativitas anak - Rahmah, Rahmah; Rahayu, Swandra; Fadhilah, Aisyah (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2024)
The purpose of the study was to find out about the Lego Robot Cardboard Box game on children's creativity. Creativity is an ability that everyone has at different levels. Children's potential can be developed. One of my creative games is the Lego Robot Cardboard Box game. The method used in this study used a pre-experiment design with a One-Group Pre-Test-Post-Test design. The results of the study showed that the t-count value obtained was 0. Then the t- count was compared with the t-table with a significance level of 5% and N 17. From the critical value for the Wilcoxon signed-rank test, it is known that the t- table value for N 17 and a significance level of 5% is 35. If t-count <t-table (0<30), it can be seen that children's creativity has increased significantly. Based on the results, Ha and Ho were rejected. Thus, it can be seen that the Cardboard Box robot game can have a significant effect on the creativity of children at the Islamic Fitrah Kindergarten in Pekanbaru.